Competencia motriz real y percibida en niños y niñas de la Patagonia Chilena: La percepción del estudian-tado y del profesorado de Educación Física (Actual and perceived motor competence in children from Chilean Patagonia: perception of the students and their physical education teachers) - Gonzalez-Huenulef, Yinali; Martino-Fuentealba, Pia; Bretz, Kathrin; Ferbol, Cristina; Carcamo-Oyarzun, Jaime (Retos, 2023)
El fomento de la competencia motriz durante la infancia es uno de los objetivos preponderantes de la Educación Física según UNESCO. Para su desarrollo es importante que el estudiantado se perciba competente, y que el profesorado perciba cuan competentes son sus estudiantes ante las tareas motrices que ofrecen en sus prácticas pedagógicas. Este estudio pretende analizar las relaciones entre la percepción del estudiantado y del profesorado de Educación Física sobre la competencia motriz real. Participaron 248 estudiantes (46% niñas; edad M=11,2; DE=0,94) de 5° y 6° año de primaria de centros educacionales de la Patagonia chilena. La competencia motriz real y percibida fueron evaluadas con el test MOBAK 5-6 y el cuestionario SEMOK, respectivamente. Para determinar relaciones se utilizó el coeficiente de Pearson; para determinar diferencias según sexo se utilizó la prueba t de Student; y para determinar la diferencia entre la competencia motriz real y la percibida, tanto del estudiantado como del profesorado, se calculó un componente de diferenciación (delta). Se encontraron relaciones significativas moderadas y débiles-moderadas entre la competencia motriz real y la percepción del estudiantado (Control de Objetos r=0.401; Control del Cuerpo r=0.402) y del profesorado de Educación Física (Control de Objetos r=0.352; Control del Cuerpo r=0.264). El profesorado (Δ=1.94) presenta una percepción más precisa que el estudiantado (Δ=2.46) solo en la competencia motriz relacionada con Control de Objetos. La percepción de competencia proporciona una visión cercana de la competencia motriz real. El profesorado de Educación Física puede pronosticar el desempeño motriz de sus estudiantes, lo que puede utilizarse como herramienta para la programación de actividades que busquen el desarrollo de la competencia motriz.Palabras Clave: competencia; percepción; habilidades motrices; desarrollo motor.Abstract. The promotion of motor competence during childhood is one of the main objectives of physical education (PE) class according to UNESCO. For its development, it is important for students to perceive themselves as competent, and for teachers to perceive how competent their students are in the motor tasks they offer in their classes. This study aims at analyzing the relationship between students’ and PE teachers’ perception of actual motor competence. A total of 248 students (46% girls; age M=11.2; SD=0.94) of 5th and 6th year of primary school from schools in Chilean Patagonia participated in the study. We assessed actual and perceived motor competence with the MOBAK 5-6 test and the SEMOK questionnaire, respectively. We used Pearson’s coefficient to determine the relationships; Student’s t-test to determine differences according to sex; and calculated a difference component (delta) to determine the difference between actual and perceived motor competence of both students and teachers. We found moderate and weak-moderate relationships between the actual motor competence and the students’ perception (Object Control r=0.401; Self-movement r=0.402), and their physical education teachers’ perception (Object Control r=0.352; Self-movement r=0.264). The teachers (Δ=1.94) present a more accurate perception than the students (Δ=2.46) only in motor competence related to object control. The perception of competence allows a closer look at the actual motor competence. Physical education teachers can predict the motor performance of their students and could use this information as a resource for the preparation of activities that aim at the development of the students’ motor competence.Keywords: competence; perception; motor skills; motor development.